Creating Legends, Kindling Hope, and Surviving – Beyond - Yin, Christina (SARE: Southeast Asian Review of English, 2022)
This hybrid memoir-collage brings together myths and folklore from Iban communities in Sarawak and deep personal loss amid the pandemic that continues to shape and reshape the lives of humans around the world. The stories of death and life, reincarnation and the mingling of the orang-utan and human populations that share life in the Bornean rainforest are teased forth in this creative nonfiction piece. Upon these layers of many truths, hope still kindles and from this flickering light, new life emerges. It seems that the world that is rebuilt from this pandemic still has room for myths and folklore. Perhaps we live by creating new legends from the true tales that help us to survive though surrounded by the invisible alien that threatens to invade our bodies, damaging and sometimes killing its hosts, trying to find a way to live in this new century. We are living in a dystopian nightmare, but we survive on the hope that there is life still, beyond.